2016
DOI: 10.1109/tdei.2015.005256
|View full text |Cite
|
Sign up to set email alerts
|

Corona degradation of the polymer insulator samples under different fog conditions

Abstract: Corona discharges resulting from the metal parts of insulators and the line hardware affect the long term performance of the polymeric insulators used for outdoor application and can lead to its eventual failure. The authors previous work, involved in developing a new methodology to evaluate the performance of polymeric shed materials subjected to corona stresses in the presence of natural fog condition, results revealed more surface hydroxylation thereby resulting in more loss of hydropobhicity. With the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It was found that the long-term field exposure yielded weaker insulator deterioration than the salt-fog chamber ageing [15], suggesting that long-term salt-fog aging may have a serious impact on the properties loss of HTV. The salt-fog aging phenomenon under corona treatment is more obvious than that without energy [16]. More hydroxylation induced by corona was found in a cold-fog condition, which may cause a hydrophobicity loss of composite insulators [17].…”
Section: Introductionmentioning
confidence: 95%
“…It was found that the long-term field exposure yielded weaker insulator deterioration than the salt-fog chamber ageing [15], suggesting that long-term salt-fog aging may have a serious impact on the properties loss of HTV. The salt-fog aging phenomenon under corona treatment is more obvious than that without energy [16]. More hydroxylation induced by corona was found in a cold-fog condition, which may cause a hydrophobicity loss of composite insulators [17].…”
Section: Introductionmentioning
confidence: 95%
“…Surface cracks may modify the mechanical and electrical properties of these insulators [ 82 ]. Several researchers have made attempts to understand corona-caused degradation using single and multiple-needle electrode test systems [ 83 , 84 , 85 ]. The purpose of multiple needles is to produce a large area of the degraded surface for different investigations, which is not possible otherwise by using a single-needle electrode arrangement.…”
Section: Role Of Fillers On Important Properties Of Polymeric Insulatorsmentioning
confidence: 99%
“…Corona varying with air-density and humidity is accompanied by UV light, heat, and gaseous by-products (ozone, NO 2 ) and corona discharges leave severe electrical strains and chemical degradation of insulators. Prolong exposure leaves polymer unusable [29]. Heat and light produce surface cracking and erosion [12].…”
Section: Sir Dielectric Loss Causesmentioning
confidence: 99%